Atropine Treatment for Hypertrophic Pyloric Stenosis: A Systematic Review and Meta-Analysis - Lauriti, Giuseppe; Cascini, Valentina; Chiesa, Pierluigi Lelli; Pierro, Agostino; Zani, Augusto (European Journal of Pediatric Surgery, 2018)
Introduction Several authors have reported the use of atropine as an alternative treatment to pyloromyotomy in infants with hypertrophic pyloric stenosis (HPS). Our aims were to review the efficacy of atropine in treating HPS and to compare atropine therapy versus pyloromyotomy.Materials and Methods Using a defined search strategy (PubMed, MEDLINE, OVID, Embase, Cochrane databases), two investigators independently identified studies reporting the use of atropine for HPS. Case reports and opinion articles were excluded. Outcome measures included success rate, side effects, and length of hospital stay. Maneuvers were compared using Fisher's exact test, and meta-analysis was conducted using RevMan 5.3. Data are expressed as mean ± standard deviation.Results Systematic review: of 2,524 abstracts screened, 51 full-text articles were analyzed. There were no prospective or randomized studies. Twelve articles (508 infants) reported HPS resolution using atropine in 402 (79.1%) patients. Atropine side effects were documented in 38/251 (15.1%) infants and included tachycardia, increased transaminases, and flushed skin. Meta-analysis: five studies compared atropine treatment (293 infants) with pyloromyotomy (537 infants). Pyloromyotomy had higher success rate (100%) than atropine (80.8%; p < 0.01) and shorter hospital stay (5.6 ± 2.3 vs. 10.3 ± 3.8 days, respectively; p < 0.0001).Conclusion Comparative but nonrandomized studies indicate that atropine is less effective than pyloromyotomy to treat infants with HPS. Currently, there is no evidence-based literature to support atropine treatment in these infants. To our knowledge, atropine should be reserved for patients unfit for general anesthesia or surgery.
Keywords: atropine; pyloromyotomy; hypertrophic pyloric stenosis; systematic review; meta-analysis